PP fibers spun with the addition of paraffin oil - Demšar, Andrej (Kovine zlitine tehnologije, 1998)
In the present study paraffin oil (10% of mass) was used as an additive in the spinning of polypropylene filament yarns on a laboratory spin-draw device. The oil was added to the polymer in the feeding zone of the extruder prior melting of the polymer. The PP filament yarns and the filament yarns to which the oil was added were spun at three different temperatures. The objective of the study was to investigate the influence of the addition of paraffin oil on the spinning process and on the properties of produced filament yarns.
Keywords: polipropilen; vlakna; dodatki; parafinsko olje; predenje